2020
DOI: 10.1093/humrep/deaa212
|View full text |Cite
|
Sign up to set email alerts
|

Should germline genome editing be allowed? The effect of treatment characteristics on public acceptability

Abstract: STUDY QUESTION To what extent do characteristics of germline genome editing (GGE) determine whether the general public supports permitting the clinical use of GGE? SUMMARY ANSWER The risk that GGE would cause congenital abnormalities had the largest effect on support for allowing GGE, followed by effectiveness of GGE, while costs, the type of application (disease or enhancement) and the effect on child well-being had moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…There has been consistently greater support for treatment than for enhancement and for the intervention in adults than in unborn children. This strong opposition towards enhancement was also observed in a Dutch adult population in 2018 (van Dijke et al 2021 ). The study by van Dijke et al ( 2021 ) has concentrated on germline genome editing and has shown that the possibility to treat congenital abnormalities positively influenced the attitude towards genome editing.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…There has been consistently greater support for treatment than for enhancement and for the intervention in adults than in unborn children. This strong opposition towards enhancement was also observed in a Dutch adult population in 2018 (van Dijke et al 2021 ). The study by van Dijke et al ( 2021 ) has concentrated on germline genome editing and has shown that the possibility to treat congenital abnormalities positively influenced the attitude towards genome editing.…”
Section: Discussionsupporting
confidence: 64%
“…This strong opposition towards enhancement was also observed in a Dutch adult population in 2018 (van Dijke et al 2021 ). The study by van Dijke et al ( 2021 ) has concentrated on germline genome editing and has shown that the possibility to treat congenital abnormalities positively influenced the attitude towards genome editing. Intervention in the human germline for non-preventive and non-therapeutic purposes (i.e., to only “improve” humans) has clearly been rejected by the European States in the Oviedo Convention (Council of Europe 1997 ).…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, Japanese users generally accepted the use of genome editing for disease-related genes; however, many were concerned about its risks [ 49 ]. Although many Dutch adults responding to a survey considered the risks of GGE to be substantially greater than its benefits, they may approve of using GGE if it is sufficiently safe and effective and used for a disease instead of enhancement [ 50 ]. In addition, another survey based on the responses from 1537 participants across 67 countries (87% of whom were White and mainly from the United States, Australia, Canada, and the United Kingdom) found that respondents generally supported GGE for medical applications, and resistance was mainly reported by people with religious beliefs or working experience in genetics [ 51 ].…”
Section: Discussionmentioning
confidence: 99%